1993
DOI: 10.1111/j.1432-1033.1993.tb18425.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutants of Methylobacterium extorquens and Paracoccus denitrificans deficient in c‐type cytochrome biogenesis synthesise the methylamine‐dehydrogenase polypeptides but cannot assemble the tryptophan‐tryptophylquinone group

Abstract: Five mutants of Methylobacterium extorquens and four mutants of Paracoccus denitrificans that have a general defect in c-type cytochrome synthesis also failed to assemble an active methylamine dehydrogenase. In all cases methanol dehydrogenase, another periplasmic enzyme, was fully active. All nine mutant strains accumulated both the heavy and light subunits of methylamine dehydrogenase to essentially wild-type levels. In all nine mutants, the heavy-subunit and light-subunit polypeptides were proteolytically p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 50 publications
2
23
0
Order By: Relevance
“…It has been shown that the TPQ cofactor in CAO (35) and the Cys-Tyr crosslinked cofactor in galactose oxidase (36) are both generated by the copperdependent autocatalytic process of the precursor proteins. On the other hand, the biosynthesis of TTQ in MADH appears to be catalyzed by an enzymatic process, because the absence of one of the genes (mauG) of the 11 genes in the mau operon prevents the maturation of TQQ (37). The biosynthetic process for CTQ in the ␥ subunit of QHNDH may involve an enzyme-mediated process as well.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the TPQ cofactor in CAO (35) and the Cys-Tyr crosslinked cofactor in galactose oxidase (36) are both generated by the copperdependent autocatalytic process of the precursor proteins. On the other hand, the biosynthesis of TTQ in MADH appears to be catalyzed by an enzymatic process, because the absence of one of the genes (mauG) of the 11 genes in the mau operon prevents the maturation of TQQ (37). The biosynthetic process for CTQ in the ␥ subunit of QHNDH may involve an enzyme-mediated process as well.…”
Section: Resultsmentioning
confidence: 99%
“…That ccm mutations have pleiotropic effects is becoming increasingly apparent. In the extracellular bacterial systems, ccm has been implicated in manganese oxidation (17,24), gluconate and 2-ketogluconate oxidation (70), methylamine oxidation (64), nicotinic acid hydroxylation (49), copper resistance (86), and the cis-trans isomerization of unsaturated fatty acids (42). Thus, future characterization of our infectivity mutants should provide new insights into ccm and cytochrome c function in particular and bacterial physiology and intracellular infection in general.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of an autocatalytic system are the biogenesis of the topaquinone cofactor in copper amine oxidases (15) and of the Cys-Tyr cofactor in galactose oxidase (16), in the latter case with the formation of a thioether linkage. An example of an enzymatic process is the biosynthesis of tryptophan tryptophylquinone in methylamine dehydrogenase, where the absence of one of the genes (mauG) of the 11 genes in the mau operon appears to prevent the maturation of tryptophan tryptophylquinone (17,18).…”
Section: Discrepancy Between Masses Measured By Maldi-tof-ms and Esi-ms-mentioning
confidence: 99%